The Shafi'i Fiqh Perspective on the Husband's Use of Dowry as Business Capital (Case Study in the Langien Settlement, Bandar Baru District, Pidie Jaya Regency) - Rifqi Darmil; Fidiatul Makfira (International Journal of Sharia Studies, 2024)
This research is motivated by the phenomenon of the use of dowry as business capital by husbands in Kemukiman Langien, Bandar Baru District, which is interesting to study because it concerns the wife's property rights, which are stipulated in Islamic law. The dowry is one of the rights of a wife, explained that the dowry is an obligatory gift from a prospective husband to a prospective wife. In Shafi'i Fiqh, ownership of the dowry is a wife's personal right that may not be exploited by anyone, including the husband. This study aims to answer the views of Shafi'i fiqh on the use of dowry as business capital, and how the use of dowry impacts the family in practice in the field. The research method used is a qualitative empirical juridical. The data sources consist of primary and secondary data consisting of three informants and three local religious figures. The data were analyzed using a descriptive method through a comparison between Shafi'i fiqh theory and empirical facts in the field. The results show that Shafi'i fiqh allows husbands to use dowry as business capital only with the permission and agreement of the wife. Utilizing a dowry with consent clearly has positive impacts, such as easing the family's economic burden and strengthening household cooperation. Conversely, using it without consent can lead to conflict and even divorce, emphasizing the importance of communication, agreement, and written documentation to protect the wife's rights. Therefore, it can be concluded that utilizing a dowry as business capital has both positive and negative potential, largely determined by open communication, clarity of agreement, and respect for the wife's rights in accordance with the principles of Shafi'i jurisprudence.